Positioning Produk Desa Hatusua Seram Bagian Barat - Sitaniapessy, Rainier H.; Asnawi, Aisah; Tehuayo, Erlinda; Pelupessy, Merry M. (Community Engagement and Emergence Journal (CEEJ), 2024)
The objectives to be achieved from the implementation of this activity are: a). growing and developing an entrepreneurial culture from MSME products in Hatusua Village b). providing motivation for MSMEs c). changing the mindset among MSMEs; d) improving the ability and skills of MSMEs to aim for product positioning. Participants in entrepreneurship training activities are MSMEs in Hatusua village consisting of 20 people. The place of activity is the Hatusua Village Meeting Building. Training on MSME product positioning will allow for increased income for MSMEs due to the highly competitive product position in the local product market